Microbiological criteria of cooked rice at point of sale from food services in the southern sector of the University of the Philippines Diliman campus - Asaldo, Karen Grace Concha (College of Home Economics, University of the Philippines Diliman, 2013)
The establishment of microbiological criteria of boiled rice at point of sale based on generated microbial results from representative sampling sites on the southern sector of the University of the Philippines Diliman campus was done. The sampling sites included a cafeteria, food stall in a food court, convenience store and a college canteen. The study was focused in university setting because of the captured audience that serves as the immediate consumer of food products in the campus. The analyzed boiled rice sample recorded a pH mean of 6.02+0.181 and Aw mean of 0.90+0.005 which attested to the high perishability of the commodity particularly when stored at ambient temperature. To establish the microbial profile of the test samples, APC and YMC were used as utility indicators, CC as quality indicator and B. cereus count as pathogenic indicator. Total mean of boiled rice was 1.8x106 cfu/g, 5.1x103 cfu/g and 3.0 MPN/g for APC, YMC and CC respectievly. For the establishment of microbial criteria, an attribute sampling was used in the study because of the unknown distribution of microorganisms in test boiled rice, and a 3-class plan was utilized. Based on the stringency of each case used, values of n and c were established: n=5 for APC, YMC and CC while n=10 for B. cereus count. All microbial parameters used c=1. The rounded values of the counts were used to establish the microbial limitsm which refers to the total mean of microbial parameters tested and M which refers to the highest count obtained from each microbial tests. The generated values were m=<107 cfu/g and M=>108cfu/g for APC, m=<104 cfu/g and M=>106cfu/g for YMC and m=<3MPN/g and M=>30MPN/g for CC. No confirmed isolate for B. cereus was obtained. There were no food borne disease outbreaks reported during the sampling period of the study, therefore, the generated microbial results were considered within the acceptable microbial limits. It is recommended that microbial results obtained should be validated by increasing the number of sampling sites to be analyzed.